Money Politic VS Political Marketing: Studi Kasus: Pemilihan Anggota Legislatif DPRD Kabupaten Pringsewu Periode 2019-2024 - Utami, Bernadhita Herindri Samodera; Herinanto, Dwi; Gumanti, Miswan; Purwanto, Bambang (Research and Development Agency Ministry of Home Affairs, 2020)
The meaning of